Improving Student's Logical Thinking Abilities And Learning Outcomes Through Guided Inquiry Model - Yuliana, Nur; Purwati, Nining; Hanapi, Hanapi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The abilities of students can affect learning outcomes. One capability that is closely related to learning outcomes is the ability to think logically which improves students’ understanding of knowledge. This study aims to determine cognitive learning outcomes and logical thinking ability of students in science subjects through the guided inquiry learning model. The quasi-experimental research was conducted with a non-equivalent pretest-posttest control group design. The population was all students of seventh grade of Miftahul Ishlah Islamic Junior high School in Mataram-Lombok.The sample was determined by cluster random sampling technique. The subjective test and the rubric of logical thinking ability were instruments used. Data were analyzed using SPSS MANCOVA, which preceded the prerequisite test, ie test for normality and homogeneity. The results showed that the guided inquiry learning model had a significant effect on the student's cognitive learning outcomes and logical thinking ability with p = 0.000, and its’ corrected mean score of learning outcomes was 95%, and corrected mean score of logical thinking ability was 71%, higher than that of student in the conventional learning model.